Remote sensing inversion of soil organic matter in cropland combining topographic factors with spectral parameters - Zou, Jinzhao; Wei, Yanan; Zhang, Yong; Liu, Zheng; Gai, Yuefeng; Chen, Hongyan; Liu, Peng; Song, Qian (Frontiers in Environmental Science, 2024)
Remote sensing has become an effective way for regional soil organic matter (SOM) quantitative analysis. Topographic factors affect SOM content and distribution, also influence the accuracy of SOM remote sensing inversion. In large region with complex topographic conditions, characteristic topographic factors of SOM in different topographic regions are unknown, and the effect of combining characteristic topographic factors with spectral parameters on improving SOM inversion accuracy remains to be further studied. Three typical topographic regions of Shandong Province in China, namely Western plain region (WPR), Central and southern mountain region (CSMR), Eastern hilly region (EHR), were selected. Topographic factors, namely Elevation, Slope, Aspect and Relief Amplitude, were introduced. Respectively, the characteristic topographic factors and spectral parameters of SOM in each region were identified. The SOM inversion models were built separately for each region by integrating spectral parameters with topographic factors. The results revealed that as for the characteristic topographic factors of SOM, none was in the WPR, E, RA, and S were in the CSMR, E and RA were in the EHR. In combination with characteristic topographic factors, the accuracy of SOM spectral inversion models improved, the calibration R 2 increased by 0.075~0.102, the RMSE (Root mean square error) decreased by 0.162~0.171 g/kg, the validation R 2 increased by 0.067~0.095, the RMSE decreased by 0.236~0.238 g/kg, and RPD (Relative prediction deviation)